Прогнозирование автоколебаний при точении - Леонов, С. Л.; Гончаров, В. Д.; Белов, Е. Б.; Белов, А. Б. (НТУ "ХПИ", 2011)
Приведена математическая модель для прогнозирования установившихся автоколебаний при токарной обработке металлов. Модель позволяет определять амплитуду и частоту колебаний, вызываемых координатной связью и нелинейностью силы резания.

The mathematical model for forecasting the established self-oscillations is resulted at turning processing metals. The model allows to define amplitude and frequency of the fluctuations caused by coordinate communication and nonlinearity of force of cutting.
Forecasting of self-oscillations at turning
Keywords: математическая модель; токарная обработка металлов; амплитуда; частота; frequency; mathematical model; amplitude